Venous malformations of the head and neck: current concepts in management. Issue 1 (January 2017) - Fowell, C.; Verea Linares, C.; Jones, R.; Nishikawa, H.; Monaghan, A.
Abstract: Low-flow venous malformations are congenital lesions and they are the third most common vascular anomaly in the head and neck. In this paper, the third in a series of three educational reviews, we discuss current trends in their management, and include a summary of common sclerosant agents used in their control.